Design of an Electric Fan with Intelligent Air Blowing System - Yao, Xin; Liao, Jinghen; Sun, Jing; Zhang, Lu; Cai, Jiaowu (Scientific Journal of Technology, 2025)
Most fans on the market currently can only oscillate within a fixed angle range. This paper presents the design of an intelligent oscillating fan that can track and oscillate based on the number of people present. When only one person is present, the fan automatically tracks their position and oscillates within a 15°range. When multiple people are present, the fan oscillates between the two individuals furthest away. Testing has demonstrated that this oscillation strategy provides an excellent user experience and has significant practical value.